Similar polycyclic aromatic hydrocarbon and genotoxicity profiles of atmospheric particulate matter from cities on three different continents. (4th May 2020) - Maselli, Bianca S.; Cunha, Virginia; Lim, Hwanmi; Bergvall, Christoffer; Westerholm, Roger; Dreij, Kristian; Watanabe, Tetsushi; Cardoso, Arnaldo A.; Pozza, Simone A.; Umbuzeiro, Gisela A.; Kummrow, Fábio
Abstract: The extractable organic material (EOM) from atmospheric total suspended particles (TSP) contains several organic compounds including non‐substituted polycyclic aromatic hydrocarbons (PAHs), alkyl‐PAHs, and nitro‐PAHs. These chemicals seem to be among the key drivers of TSP genotoxicity. We have shown previously that the mutagenic potencies of the EOM from Limeira, Stockholm, and Kyoto, cities with markedly different meteorological conditions and pollution sources are similar. Here we compare the profiles of non‐substituted PAHs (27 congeners), alkyl‐PAHs (15 congeners), and nitro‐PAHs (7 congeners) from the same EOM samples from these cities. We also compared the genotoxicity profiles using comet and micronucleus assays in human bronchial epithelial cells. The profiles of PAHs, as well as the cytotoxic and genotoxic potencies when expressed in EOM, were quite similar among the studied cities. It seems that despite the differences in meteorological conditions and pollution sources of the cities, removal, mixing, and different atmospheric transformation processes may be contributing to the similarity of the PAHs composition and genotoxicity profiles. More studies are required to verify if this would be a general rule applicable to other cities. Although these profiles were similar for all three cities, the EOM concentration in the atmospheres is markedly different. Thus, the population of Limeira (∼10‐fold more EOM/m 3 than Stockholm and ∼6‐fold more than Kyoto) is exposed to higher concentrations of genotoxic pollutants, and Kyoto's population is 1.5‐fold more exposed than Stockholm's. Therefore, to reduce the risk of human exposure to TSP genotoxins, the volume of emissions needs to be reduced.